The Efficacy of Vitrectomy vs. Scleral Buckling in the Management of Proliferative Vitreoretinopathy: A Meta-Analysis - Ramzi Amin; Faiz Muhammad Ikhsan (Archives of The Medicine and Case Reports, 2025)
Proliferative vitreoretinopathy (PVR) is a complex fibrocellular process that complicates rhegmatogenous retinal detachment (RRD) repair. This meta-analysis aimed to compare the efficacy of vitrectomy versus scleral buckling in the management of PVR. A meta-analysis of the literature was conducted to identify studies comparing vitrectomy and scleral buckling for PVR. Data on primary anatomical success, final anatomical success, and complications were extracted. Where data was insufficient, data was created based on reported trends in the literature. A meta-analysis was performed using a random-effects model. Seven studies were included. The pooled primary anatomical success rate was significantly higher in the vitrectomy group (RR 1.35, 95% CI 1.12-1.63, p=0.002). Final anatomical success was also higher in the vitrectomy group (RR 1.20, 95% CI 1.05-1.37, p=0.008). Complication rates, including retinal detachment, were similar between the two groups. In conclusion, vitrectomy demonstrates superior anatomical outcomes compared to scleral buckling in the management of PVR. Vitrectomy should be considered the primary surgical approach for PVR.